GUIDELINES FOR SIGNIFICANT CORPORATE ACTIVITIES OF STATE-OWNED ENTERPRISES: MANAGEMENT OF ADDITIONAL STATE CAPITAL, RESTRUCTURING, AND BUSINESS DEVELOPMENT STRATEGIES TO ENSURE THE SUSTAINABILITY AND GROWTH OF STATE-OWNED ENTERPRISES - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
This study analyses the effectiveness of the Guidelines for Significant Corporate Activities of State-Owned Enterprises in integrating the management of Additional State Capital (PMN), organisational restructuring, and business development strategies to ensure the sustainability and growth of State-Owned Enterprises. Using a qualitative literature review approach with content analysis of the latest regulations (Minister of State-Owned Enterprises Regulations PER-01/MBU/07/2024, PER-02/MBU/03/2023, PER-03/MBU/12/2023) and over 90 national and international academic references, the study found that the synergy of these three elements successfully increased the average ROE by 12-15%, EBITDA margin by 15%, and ESG scoring to 70/100 in strategic holdings such as MIND ID, Bio Farma, and Telkom Group. The main challenges include the independence of PMN evaluation, cultural resistance to restructuring, and regulatory uncertainty that hinders business agility. Strategic recommendations include PMN clawback clauses, blockchain monitoring digital dashboards, and a 10% PMN State Venture Fund for deep tech/green investment to achieve 20 SOEs in the global top 500 by 2030, in line with Indonesia's Golden Vision 2045.